Phylogenetic assessment of heterotrophic bacteria from a water distribution system using 16S rDNA sequencing - Tokajian, Sima T. (2005)
Determination of a heterotrophic plate count (HPC) for drinking-water samples alone is not enough to assess possible health hazards associated with sudden changes in the bacterial count. Speciation is very crucial to determine whether the population includes pathogens and (or) opportunistic pathogens. Most of the isolates recovered from drinking water samples could not be allocated to a specific phylogenetic branch based on the use of conventional diagnostic methods. The present study had to use phylogenetic analysis, which was simplified by determining and using the first 500-bp sequence of the 16S rDNA, to successfully identify the type and species of bacteria found in the samples. Gram-positive bacteria α-, β-, and γ-Proteobacteria were found to be the major groups representing the heterotrophic bacteria in drinking water. The study also revealed that the presence of sphingomonads in drinking water supplies may be much more common than has been reported so far and thus further studies are merited. The intermittent mode of supply, mainly characterized by water stagnation and flow interruption associated possibly with biofilm detachment, raised the possibility that the studied bacterial populations in such systems represented organisms coming from 2 different niches, the biofilm and the water column.Key words: intermittent water supply, 16S rDNA, biofilm, water column.